SCIENCE LEARNING TO DEVELOP CRITICAL THINKING IN ELEMENTARY SCHOOL STUDENTS - Friani, Devi Anggi; Marheni Rayung Puspaningrum; Arina Wanawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the implementation of science learning in developing critical thinking skills of elementary school students. The problem addressed in this research is the low level of students’ critical thinking skills caused by teacher-centered learning and lack of meaningful learning experiences. This study employed a qualitative descriptive approach with subjects consisting of fifth-grade students and teachers at an elementary school. Data were collected through observation, interviews, and documentation. The findings indicate that student-centered, contextual, and activity-based science learning significantly improves students’ critical thinking skills. This improvement is reflected in the increase of pretest and posttest scores with a moderate N-Gain category, as well as enhanced student participation in questioning, analyzing, and concluding. The use of experiments, cooperative learning, and contextual approaches based on local potential contributes to meaningful learning experiences and strengthens students’ understanding. Therefore, innovative and interactive science learning plays a crucial role in fostering critical thinking skills in elementary education.